2009
DOI: 10.1007/s10238-009-0071-z
|View full text |Cite
|
Sign up to set email alerts
|

Empty sella and primary autoimmune hypothyroidism

Abstract: In order to assess the association between empty sella (ES) and primary autoimmune hypothyroidism, and the possibility of a common pathogenesis. We retrospectively studied all patients with presumed ES diagnosed in the last 20 years, most of whom were treated by our Endocrinology Department. Subjects with a known etiology were excluded. Incomplete records or those with a doubtful diagnosis were also excluded. A total of 56 subjects were included in the study. ES was diagnosed by pituitary MRI. The measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
(54 reference statements)
1
5
0
Order By: Relevance
“…Different etiologies may be present among patients diagnosed with primary ESS (5). García-Centeno et al (8) reported HT frequency as 26.7% among primary ESS patients (9). In the present study, the frequency of HT was 22.2% among primary ESS patients.…”
Section: Discussionsupporting
confidence: 56%
“…Different etiologies may be present among patients diagnosed with primary ESS (5). García-Centeno et al (8) reported HT frequency as 26.7% among primary ESS patients (9). In the present study, the frequency of HT was 22.2% among primary ESS patients.…”
Section: Discussionsupporting
confidence: 56%
“…2 In a recent series of 56 patients with empty sella syndrome, a possible outcome of lymphocytic hypophysitis, AITD was found in 27%, but local controls were not included. 8 An association has also been reported between AITD and isolated growth hormone deficiency, which occurred in 5% of patients and could reflect an autoimmune hypophysitis, 9 but a recent study has been unable to confirm such a high prevalence of growth hormone deficiency in AITD. 10 In idiopathic hypoparathyroidism, there is no clear increase in AITD, despite growing evidence that the calcium-sensing receptor is the target of autoimmunity in at least a subset of patients.…”
Section: Autoimmune Endocrinopathiesmentioning
confidence: 99%
“…AITD appears to be increased in patients with lymphocytic hypophysitis but exact data are not available given the rarity of this condition 2 . In a recent series of 56 patients with empty sella syndrome, a possible outcome of lymphocytic hypophysitis, AITD was found in 27%, but local controls were not included 8 . An association has also been reported between AITD and isolated growth hormone deficiency, which occurred in 5% of patients and could reflect an autoimmune hypophysitis, 9 but a recent study has been unable to confirm such a high prevalence of growth hormone deficiency in AITD 10 …”
Section: Autoimmune Disease Associations With Aitdmentioning
confidence: 99%
“…In total, 165 subjects were included from the 29 studies. Of these, 46 subjects were in studies on primary hypothyroidism [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] (i.e. in which hypothyroidism was related to ID), 97 subjects in studies on congenital hypothyroidism [67][68][69][70][71][72][73][74][75][76][77], 3 subjects in a study of endemic cretinism [78], 11 subjects in a study of subclinical hypothyroidism [79,80] and 8 subjects in a study of perinatal hypothyroidism [80] (Figure 2).…”
Section: Sample Sizementioning
confidence: 99%
“…Ten studies gave implicit inclusion/exclusion criteria through the description of the characteristics of the sample and five gave them explicitly [67,69,74,76,77]. Reasons for rejection were patients with unrelated disorders which may affect cerebral function or development such as chromosomal or metabolic Only 7 MRI studies utilised contrast enhancement; Gadolinium was used in each of these [55][56][57][60][61][62]65]. Both MRS studies [67,72] used shimming techniques and water suppression chemical shift selection pulses but only one study discussed the additional use of Stimulated Echo Acquisition Mode (STEAM) [72].…”
Section: Blinding Randomisation and Inclusion/exclusion Criteriamentioning
confidence: 99%